Pemanfaatan Sabut Pinang sebagai Kombinasi Filter Multi Media-Sabut Pinang (FMM-SP) di Perumahan Valensia Muaro Jambi dan Uji Kualitas Air Bersih - Safita, Reny; Kurniawan, Fery; Deliza, Deliza (Jurnal Riset Kimia, 2021)
This study aims to help the residential community of Valencia, Muaro Jambi to get clean water using filter multi media-sabut pinang (FMM-SP).Multimedia filtration is a method of water treatment by utilizing soil as the main medium which is shaped like brick blocks and arranged alternately between zeolites.The LMM-FSP reactor is made of used gallons, 40 cm high, 28 cm in diameter, containing brick blocks (12x7x4) cm consisting of a mixture of volcanic soil, charcoal, areca fiber, iron powder (70 :10 :10: 5) %, permeable layer used zeolite (1-3 mm). The samples came from the wells of residents of Valencian housing, Muaro Jambi, Jambi City. The research was carried out with variations in the mass of areca nut into the filter, flow rates of 5, 10, 15, 20 mL/minute and two ways, namely aeration and non-aeration. FMM-SP efficiency for the aeration process at a flow rate of 5 ml/min with pH parameters; Smell; Nitrite; Nitrate; turbidity; Mn; Fe in order is 7.5; Odorless, 60.30%; 59.33%; 59.33%; 70.10%; 73.20%, and in non-aerated pH 7.3; Odorless; 50.82%; 48.37%; 60.91%, Fe 61.20% From all the efficiency values for decreasing the parameters, it can be said that it meets the requirements for clean water.